Síndrome congênita associada ao Zika vírus: além da microcefalia - Oliveira, Marco Antonio Valadares (2019)
Introduction: in October 2015, an international alert was issued for an outbreak of congenital microcephaly on Zika virus (ZIKV) infection, recently detected in Brazil, with the objective of reducing the prevalence of microcephaly at birth in the country. The absence of new cases of microcephaly in the affected regions, together with a clinical picture and common morphological alterations, led to the need to respond to a new clinical syndrome associated with a congenital infection that was not in agreement with the differential diagnosis of microcephaly. Objectives: to describe a congenital syndrome associated with a maternal infection by ZIKV and to evaluate the encephalic changes of the microcephalic population studied, as well as ophthalmologic alterations, echocardiographic findings and other malformations. Patients and Methods: descriptive crosssectional observational study, with non-random and consecutive sample. It included 65 infants diagnosed with microcephaly and attended at the University Hospital of the Federal University of Sergipe. The data sheet of the microcephaly service was the source for the clinical information, as well as the neonatal period and gestation data. Transfontanel ultrasonography was performed in all patients in the sample. Ophthalmologic evaluation occurred in 62 children of the group, while 59 were submitted to echocardiography. Quantitative and categorical variables were expressed according to the best suitability. For the outcome-variables, the frequency estimation was carried out with its respective Confidence Interval to 95%, using the Bootstrap technique. Results: there was a predominance of full-term, female and vaginal delivery. There was also a predominance of adequacy of birth weight and a total absence of perinatal damage described. In less than half of the mothers there was a positive history of exanthema, fever and polyarthralgia; but there was a predominance of these reports in the first trimester of gestation. A significant majority (80.0%) was classified as severe microcephaly. Otorhinolaryngological changes in the posterior segment were predominant, with atrophy of the retinal pigment epithelium (24.2%) and chorioretinitis (22.6%). Alterations in the anterior segment were also described, as well as pathological strabismus and nystagmus. Bilateral cryptorchidism was reported in 28.6% of the boys' population. Orthopedic alterations were described in 27.7% of the patients, with emphasis on multiple arthrogryposes (6.2%). The most frequent echocardiographic findings were patent foramen ovale (42.4%) and patent ductus arteriosus (10.2%). Cerebral atrophy (75.4%), calcifications (73.8%), corpus callosum dysgenesis (70.8%) and ventricular dilatation (64.6%) and lysencephaly (61.5%). Conclusions: the ophthalmologic alterations described are more serious than those reported for other causes of congenital infection associated with microcephaly, especially for funduscopy alterations. It also awakens to other malformations not yet documented for congenital virus infection, such as echocardiographic findings and cryptorchidism. Orthopedic and encephalic alterations agree with recent literature reports on the subject.